Efektivitas Sistem Informasi Wakaf (SIWAK) sebagai Strategi Mengurangi Sengketa dan Percepat Sertifikasi Tanah Wakaf di Surabaya - Santoso, Yusuf Agus; Fahrullah, A'rasy (Jurnal Ekonomika dan Bisnis Islam, 2020)
The purpose of this research is to find out how the effectiviveness of the waqf information system as a strategy to reduce disputes and accelerate the certification of waqf land in Surabaya. This study uses a qualitative descriptive approach by understanding the subject phenomenon. The data collection rechniques using observation, interviews and documentation. The results of this research can be concluded that the waqf information system (SIWAK) has been effective and can reduce waqf land disputes in Surabaya. But only on waqf land that already has waqf pledge deed (AIW). With SIWAK, the ministry of religion (KEMENAG) can also facilitate the certification of waqf land in Surabaya. With the assistance of coun selors from the religious affairs office (KUA) to follow up all available waqf land. If a waqf land is found that has pledged but not entered into the waqf information system (SIWAK) the data input will be entered into the system. Honever, if a pledge is not yet made, the ministry of religion (KEMENAG) will come and then be directed to immediately pledge.